The Computer in Auditing–The Use of Test Data. - Malcom, Robert E.; Griffin, Charles H. (The Accounting Review, 1967)
Reviews the book "The Computer in Auditing: The Use of Test Data," by Gerald Wohl and Michael D'Angelico.